Learning through Digital Technology: Role of National and International Education Teachers - Al-Barakat, Ali Ahmad; AlAli, Rommel; Al Karasneh, Samih Mahmoud; Alakashee, Bushra Ahmad; Al-Qatawneh, Sami Sulieman; El-Mneizel, Abdalla Falah; Al Sa, Najah Rajeh; Alhawamdeh, Mohammed (Journal of International Students, 2023)
The main aim of this study was to examine how digital education can enhance the learning of young children from both the host country and international backgrounds. The study sample consisted of 53 female childhood education teachers, including 23 national and 30 international teachers from the Emirate of Sharjah in the United Arab Emirates. The participants were selected using the available sampling method. To achieve the study’s goal, a carefully crafted, semi structured interview was created, considering its validity and reliability. The study revealed numerous consequences linked to learning through digital tools, which enhance the quality of education for both local and international children in the host country. The results highlighted the importance of cognitive learning through digital platforms as well as the development of emotional aspects.